2009
DOI: 10.1021/je9003405
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic−Hydrophilic Solvation of Variously Substituted N-Alkylureas in Aqueous Solution: A Calorimetric Study at a Temperature of 298.15 K

Abstract: Enthalpies of solution, ∆ sol H m , in water, of some di-, tri-, and tetra-substituted N-alkylureas were measured by isothermal calorimetry at T ) (296.84, 306.89, and 316.95) K. The molar enthalpies of solution at infinite dilution (i.d.), ∆ sol H m ∞ , and molar heat capacity changes for the solution process at i.d., ∆ sol C p,m ∞ , were obtained at T ) 298.15 K. Molar enthalpies of solvation, ∆ solv H m ∞ , and partial molar heat capacities, C p,2 ∞ , at i.d. were then calculated from the molar enthalpies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 50 publications
4
21
0
Order By: Relevance
“…The 1,5-pentanediol solution was chosen for this comparison because the additional methylene groups of that additive are more disruptive of the native structure of liquid water, relative to the 1,3-propanediol additive. 92,93 Figure S10 of the supplementary material compares the XAS spectra of [Cu(aq)] 2+ in 1M HClO 4 solution and in the 1,5-pentanediol solution with 0.6M HClO 4 . The XANES spectra are nearly superimposable [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The 1,5-pentanediol solution was chosen for this comparison because the additional methylene groups of that additive are more disruptive of the native structure of liquid water, relative to the 1,3-propanediol additive. 92,93 Figure S10 of the supplementary material compares the XAS spectra of [Cu(aq)] 2+ in 1M HClO 4 solution and in the 1,5-pentanediol solution with 0.6M HClO 4 . The XANES spectra are nearly superimposable [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical sample descriptions are given in Table . For the purpose of this investigation, TU and 1,3-DMU were purified by recrystallization from absolute ethanol (Fluka puriss, x ≥ 0.998), while 1,3-DMTU was purified by recrystallization from anhydrous tetrahydrofuran (Fluka puriss, x ≥ 0.999) followed with slow precipitation by the addition of diethyl ether (Fluka, ACS reagent, x > 0.995) to suppress the supercooling effect, according to the recommendations of Della Gatta and Badea et al , All compounds were then dried to constant mass under reduced (down to 10 Pa) pressure at T ≈ 310 K.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the results of heat capacity, isopiestic and enthalpy-related measurements, it was shown that the hydrogen-bonding ability of the functional grouping −N(H)–C(S)–N(H)– can be modulated by the insertion of alkyl substituents. Herewith the “structural topography” of such hydrophobic moieties plays an important role in determining their bonding/hydration as found for U and its N -alkyl-substituted derivatives. ,,, As a consequence, thioureas are widely utilized in the field of molecular recognition, , as well as for the construction of nanostructured materials and pharmaceuticals. , Moreover, taking into account the fact that ureas and thioureas differ in the molecule polarity (dipole moments of the latter were found to be slightly higher), a comparative analysis of volumetric properties of aqueous U, TU, and their alkyl-substituted derivatives could yield useful information on the interaction of >CO and >CS moieties with the surrounding water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009 we identified more than 400 articles after searching Web of Science, PubMed, SciDir and OVID databases using ‘isothermal AND titration AND calorimetry’ or ITC or ‘Isothermal Titration Calorimetry’ search terms. These have been classified into the following categories: Pre‐2009 references cited in the text and review articles 1–43 Protein‐protein and protein‐peptide interactions 44–124 Protein/peptide‐small molecule interactions 125–218 Protein/peptide‐metal ion interactions 219–253 Protein/peptide‐nucleic acid interactions 254–273 Protein/peptide‐lipid interactions 274–292 Protein/peptide‐polysaccharide interactions 293–316 Nucleic acid‐small molecule interactions 317–348 Small molecule interactions …”
Section: Introductionmentioning
confidence: 99%